A cytogenetic analysis of chromosomal region 31 of Drosophila melanogaster. - Clegg, N.J.; Whitehead, I.P.; Brock, J.K.; Sinclair, D.A.; Mottus, R.; Stromotich, G.; Harrington, M.J.; Grigliatti, T.A. (Genetics, 1993)
Cytogenetic region 31 of the second chromosome of Drosophila melanogaster was screened for recessive lethal mutations. One hundred and thirty nine new recessive lethal alleles were isolated that fail to complement Df(2L)J2 (31A-32A). These new alleles, combined with preexisting mutations in the region, define 52 complementation groups, 35 of which have not previously been described. Among the new mutations were alleles of the cdc2 and mfs(2)31 genes. Six new deficiencies were also isolated and characterized identifying 16 deficiency subintervals within region 31. The new deficiencies were used to further localize three loci believed to encode non-histone chromosomal proteins. Suvar(2)1/Su(var)214, a dominant suppressor of position-effect variegation (PEV), maps to 31A-B, while the recessive suppressors of PEV mfs(2)31 and wdl were localized to regions 31E and 31F-32A, respectively. In addition, the cytological position of several mutations that interact with heterochromatin were more precisely defined.